MODEL WORD-OF-MOUTH DALAM KOMUNIKASI PEMASARAN PERGURUAN TINGGI - Yulista, Yera (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2012)
Institutions of higher education can be promoted through Word-of-Mouth’s marketing communication technique which is a technique that requires consumers to promote a product to others. Word-of-mouth Marketing can be done through interpersonal communications. Personal proximity factors, situational and interpersonal communication approach among communicators have an influence in deciding an act of communication. The purpose of this study to find Word-of-mouth Marketing communicationsmodel in Member Get Student program of Mercu Buana University. This study uses a type of  exploratory case studies. The results showed that the communication actors (who are recommended) still consider personal and situational factors of other actors (who recommend) before making the decision to attend Mercu Buana University. Interpersonal communication activity is quite instrumental in the formation of Word-of-mouth  Member Get Student model, while Riley and Riley’s communication model is the foundation base. Keywords: word-of-mouth, interpersonal communication, Riley and Riley’s communication model.